2023
DOI: 10.3390/jpm13030381
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Incidental Durotomy during Full-Endoscopic Lumbar Decompression Surgery in Relation to Intraoperative Epidural Pressure Measurements

Abstract: Background: Seizures, neurological deficits, bradycardia, and, in the worst cases, cardiac arrest may occur following incidental durotomy during routine lumbar endoscopy. Therefore, we set out to measure the intraoperative epidural pressure during lumbar endoscopic decompression surgery. Methods: We conducted a retrospective observational cohort study to obtain intraoperative epidural measurements with an epidural catheter-pressure transducer assembly through the spinal endoscope on 15 patients who underwent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Increasing the input water pressure to improve water output is not a good trick. If there was not good water output already, just putting water input in higher pressure will cause the cervical epidural pressure to increase, which may increase intracranial pressure [40][41][42]. Clinically sufficient water pressure can be achieved in a setting where two saline bags are placed 60-70 cm higher under natural gravity from the patient's back level in the prone position on the surgical table.…”
Section: Fluent Water Outputmentioning
confidence: 99%
“…Increasing the input water pressure to improve water output is not a good trick. If there was not good water output already, just putting water input in higher pressure will cause the cervical epidural pressure to increase, which may increase intracranial pressure [40][41][42]. Clinically sufficient water pressure can be achieved in a setting where two saline bags are placed 60-70 cm higher under natural gravity from the patient's back level in the prone position on the surgical table.…”
Section: Fluent Water Outputmentioning
confidence: 99%
“…Although the exact mechanism of seizures during fully endoscopic spine surgery is still undetermined, factors such as infusion fluid containing cefazolin, infusion rate, prolonged operative time, dural tear, and sevoflurane anesthesia may increase the risk of seizures [46]. Symptoms and signs, such as headache, neck pain, seizures, elevated blood pressure, or bradycardia, should be carefully monitored in patients [49,50]. Lin et al [46] reported the cases of seizures during full-endoscopic lumbar surgery and found that a socalled red flag sign-characterized by uncontrollable hypertension combined with a decreasing pulse rate-occurred in all 3 patients who experienced a seizure.…”
Section: Intraoperative Seizurementioning
confidence: 99%
“…Although not definitively established, this phenomenon bears similarity to the Cushing reflex, a cardiovascular response to compensate for increased intracranial pressure. This reflex sometimes occurs during endoscopic brain surgery, wherein the working space inside the brain is maintained with infused water pressure [49,50]. Previously, when a dural tear occurred during fully endoscopic spine surgery, 3 of 15 patients experienced seizures, and 1 of the 3 patients exhibited intracranial air on a postoperative CT scan [50].…”
Section: Intraoperative Seizurementioning
confidence: 99%
See 1 more Smart Citation